Analisis Kualitas Pelayanan Publik Di Kelurahan Cipaganti Kecamatan Coblong Kota Bandung - Aditia Mulawarman; Soeganda Priyatna; Sahroni Sahroni (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
The background of this research is that the quality of public services shown by employees in Cipaganti Village, Coblong District, Bandung City, has not been running optimally. This study aims to find out how the quality of public services is shown by employees in Cipaganti Village, Coblong District, Bandung City, as well as what factors hinder the quality of public services in Cipaganti Village, Coblong District. The variables in this study are the quality of public services which consist of indicators of physical evidence, reliability, responsiveness, assurance, and empathy. The type of research used is qualitative research. The research method used is descriptive method. Data collection techniques using a research questionnaire. Data collection techniques used observation and structured interviews with research informants. The data analysis technique used is descriptive analysis. The results of the study show that overall the quality of service shown by employees in Cipaganti Village, Coblong District, Bandung City is quite good, although there are still a number of things that must be considered and improved by Cipaganti Village, Coblong District, Bandung City.